After the Escuminac Disaster: Poverty and Paternalism in Miramichi Bay, New Brunswick - Rudin, Ronald (Acadiensis)

(untitled) (Department of History at the University of New Brunswick, 2023)
In June 1959, the fishing fleet leaving from the wharf at Escuminac in northeastern New Brunswick was struck by a hurricane resulting in the deaths of 35 men. The Escuminac Disaster was one of the worst work-related disasters in the province’s history, creating a significant challenge for dependents left behind with limited resources. In response, provincial leaders – both secular and religious – created the New Brunswick Fishermen’s Disaster Fund. The administrators of the fund, mostly well-to-do and English-speaking, exhibited great difficulty in understanding the survival strategies employed by families, all of whom were poor and many of whom were Acadian.